1983
DOI: 10.3102/00346543053003415
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Elementary Children’s School Roles and Sex Roles on Teacher Attitudes: An Interactional Analysis

Abstract: In this paper, teachers' attitudes toward children are examined from the perspective of role theory. Based on existing analyses of the school as a social system, three school roles for children are formulated: Pupil, receptive learner, and active learner. Their relationship to the hidden and academic curricula of the school is discussed. The extant literature in three major areas of research on teacher attitudes is analyzed in terms of their interactions with each of the three children's school roles and with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
30
0
5

Year Published

1987
1987
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(36 citation statements)
references
References 33 publications
(70 reference statements)
1
30
0
5
Order By: Relevance
“…The «attachment» children know how to reinforce the work of the teacher, they require very little attention (Silberman, 1969), display appropriate behaviors in the classroom (Good and Brophy, 1972), are achievers, sociable, cooperative (Garner & Bing, 1973), passive, dependent and tidy (Helton & Oackland, 1977). These characteristics, closely compatible with those approved in the school environment (Kedar-Voivodas, 1983) could facilitate the child's adjustment to an environment where achievement and conformism are highly supported (Bertrand & Valois, 1982).…”
Section: Teachers Attitudes and School Adjustmentmentioning
confidence: 84%
See 2 more Smart Citations
“…The «attachment» children know how to reinforce the work of the teacher, they require very little attention (Silberman, 1969), display appropriate behaviors in the classroom (Good and Brophy, 1972), are achievers, sociable, cooperative (Garner & Bing, 1973), passive, dependent and tidy (Helton & Oackland, 1977). These characteristics, closely compatible with those approved in the school environment (Kedar-Voivodas, 1983) could facilitate the child's adjustment to an environment where achievement and conformism are highly supported (Bertrand & Valois, 1982).…”
Section: Teachers Attitudes and School Adjustmentmentioning
confidence: 84%
“…This higher percentage of school maladjustment observed among boys seems to be closely linked to the teacher's perception of the student and to the type of contact established between them (Gilly, 1980). It is often reported that boys experience more negative interactions with the teachers (Brophy & Evertson, 1981;Kedar-Voivodas, 1983), are more frequently rejected (Brophy & Good, 1974;Good & Brophy, 1972;Willis & Brophy, 1974) and are perceived more negatively by them (Clift & Sexton, 1979;Gilly, 1980;Hartley, 1978;Stevenson, Parker, Wilkinson, Hegion, & Fish, 1976). Effectively, when we consider the overall evaluation of teachers, taking into account the sex of the students, boys are perceived as being less obedient, less hard-working, less cooperative (Clift & Sexton, 1979), less adapted to the classroom situation and less likely than girls to experience academic success (Stevenson et al, 1976).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…For example, children classified as rejected were rated as being more physically aggressive (e.g., hitting or pushing others) as well as relationally aggressive (e.g., says mean things to others) than were the popular stars and teacher's pets. From the teachers' point of view, classroom aggression interferes with their work, and these behaviors not only challenge their authority (Kedar-Voivodas, 1983) but also threaten the personal safety of others. Teachers have the responsibility to protect their students from physical injury inflicted by other students and there may be considerable pressure on the teachers when they must deal with it.…”
Section: Predictions Of Teacher and Peer Preferences Among Status Groupsmentioning
confidence: 99%
“…Examining these variables provides further context for the proposed inquiry framework. Role influences include attitudes and beliefs (Kedar-Voivodas, 1983;Kinchin, 2004;Lyons, 1990), norms and expectations (Ryu & Sandoval, 2010;Webb, 2009), experience (Eick & Reed, 2002;Kagan, 1992;Knowles, 1992), and social factors (Chandler & Helm, 1984;Kohlberg, 1969;Reiman & Peace, 2002;Selman, 1980;Yackel, Cobb, & Wood, 1991;Zack & Graves, 2001). …”
Section: Role Theorymentioning
confidence: 99%